2012
DOI: 10.1187/cbe.12-01-0003
|View full text |Cite
|
Sign up to set email alerts
|

Students Fail to Transfer Knowledge of Chromosome Structure to Topics Pertaining to Cell Division

Abstract: Cellular processes that rely on knowledge of molecular behavior are difficult for students to comprehend. For example, thorough understanding of meiosis requires students to integrate several complex concepts related to chromosome structure and function. Using a grounded theory approach, we have unified classroom observations, assessment data, and in-depth interviews under the theory of knowledge transfer to explain student difficulties with concepts related to chromosomal behavior. In this paper, we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 39 publications
2
47
0
3
Order By: Relevance
“…Notwithstanding the fact that low performers struggle with integrating new with existing knowledge during their learning and with applying basic science knowledge in practice, this study suggests that a lack of appropriate SRL also impacts their response to failure. The findings demonstrate that maladaptive SRL behaviours, such as the normalising of failure, a lack of reflection on action and the external attribution of failure, prevent students from overcoming failure appropriately and effectively confine them to a cycle of repeated failure (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the fact that low performers struggle with integrating new with existing knowledge during their learning and with applying basic science knowledge in practice, this study suggests that a lack of appropriate SRL also impacts their response to failure. The findings demonstrate that maladaptive SRL behaviours, such as the normalising of failure, a lack of reflection on action and the external attribution of failure, prevent students from overcoming failure appropriately and effectively confine them to a cycle of repeated failure (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common issues is student misunderstanding about the relationship between genes, alleles and chromosomes. For example, Lewis and Kattman pointed out that many students think of genes as “particles” (15), a phenomenon we have observed in our own work exploring knowledge transfer with advanced biology students (21). Students also mistakenly believe that genes are only present in a cell when they are actively being expressed or are needed for that particular cell (6, 25).…”
Section: Introductionmentioning
confidence: 79%
“…Together, these issues make the learning of cell biology rather uninspiring for students. Moreover, previous studies have reported that students fail to make connections across different topics, leading them to only partially appreciate how nature functions (Mil, Boerwinkel, and Waarlo 2011;Newman, Catavero, and Wright 2012). From my previous experience, I have noted that students tend to study topics in isolation, with little or no regard for functional interactions among them.…”
Section: Introductionmentioning
confidence: 89%